Microbiological assay for the determination of cefpirome in raw material and injectable preparation - Oppe, Tércio Paschke; Menegola, Julia; Schapoval, Elfrides E.S. (Drug Analytical Research, 2026)
Cefpirome is a fourth-generation cephalosporin active against a broad spectrum of gram-negative and gram-positive bacterial infections. The present work describe the development and validation of a simple, sensitive and specific agar diffusion bioassay applying cylinder-plate method for quantification of cefpirome in raw material and powder for injectable preparation. The validation method yielded good results and included linearity, precision, accuracy and specificity. The assay is based on the inhibitory effect of cefpirome upon the strain of Kocuria rizophila ATCC 9341 as the test microorganism. The result of assay were treated statistically by ANOVA and the response graphs for standard and sample solutions were linear (r = 0.9948) in the range of 0.3 – 1.2 µg mL-1, precise (intra-assay: RSD = 0.11; inter-assay: RSD = 0.18) and accurate (mean recovery value = 99.41%). A preliminary stability study of cefpirome showed that the microbiological assay is specific for the determination cefpirome in the presence of its degradation products. The proposed microbiological method allows the quantitation of cefpirome in pharmaceutical dosage form and raw material and can be used for the drug analysis in routine quality control.